2014
DOI: 10.1371/journal.pone.0110046
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Mapping for Kernel and Malting Quality Traits Using Historical European Barley Records

Abstract: Malting quality is an important trait in breeding barley (Hordeum vulgare L.). It requires elaborate, expensive phenotyping, which involves micro-malting experiments. Although there is abundant historical information available for different cultivars in different years and trials, that historical information is not often used in genetic analyses. This study aimed to exploit historical records to assist in identifying genomic regions that affect malting and kernel quality traits in barley. This genome-wide asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 92 publications
(97 reference statements)
7
46
1
Order By: Relevance
“…The germplasm studied here is composed of germplasm, which was clustered according to inflorescence type, geographic origin, and breeding history. Previous studies also indicated spike morphology (two‐rowed versus six‐rowed), geographic origin, domestication or breeding history, growth habits and vernalization requirements (winter versus spring) as the major cluster factors of barley germplasm . This study also revealed a considerable level of overlap in ICARDA germplasm with NDSU lines at one end and to Ethiopian breeding lines at the other end.…”
Section: Discussionsupporting
confidence: 64%
“…The germplasm studied here is composed of germplasm, which was clustered according to inflorescence type, geographic origin, and breeding history. Previous studies also indicated spike morphology (two‐rowed versus six‐rowed), geographic origin, domestication or breeding history, growth habits and vernalization requirements (winter versus spring) as the major cluster factors of barley germplasm . This study also revealed a considerable level of overlap in ICARDA germplasm with NDSU lines at one end and to Ethiopian breeding lines at the other end.…”
Section: Discussionsupporting
confidence: 64%
“…Malting quality is a complex trait that consists of several components. The main objectives for malting barley breeding are the improvement of grain quality traits such as malt extract and protein content, and grain physical traits including grain formation and weight and glume content (Matthies et al, 2014). It should be emphasized that during the process of barley breeding, grain quality is mainly tested in later generations, which additionally underlines the importance of grain weight and size in development of new malting barley cultivars.…”
Section: According Tomentioning
confidence: 99%
“…GWAS has several advantages over traditional QTL analysis, such as higher diversity, better utility of the identified QTL across diverse germplasm, and reduced time required for population development [1012]. GWAS has been successfully employed in many plants, such as Arabidopsis [13], maize [10, 14], barley [15, 16], wheat [17, 18], rice [19], oat [20], sorghum [21] and soybean [11, 22]. In cotton, a few genetic studies using GWAS have been reported [2, 4, 23, 24].…”
Section: Introductionmentioning
confidence: 99%